Experimental study on influence of stack effect on fire in the compartment adjacent to stairwell of high rise building - Shi, Wen Xi; Ji, Jie; Sun, Jin Hua; Lo, S. M.; Li, Lin Jie; Yuan, Xiang Yong (Journal of Civil Engineering and Management, 2014)
In this paper, to study the influence of stack effect on fire in the compartment adjacent to a stairwell, a set of experiments were conducted by varying the pool size, top vent state and bottom vent size in a 1/3 scaled 12-layer-stairwell configuration. The phenomenon of methanol flame tilting in the fire room was observed and studied. Results showed that the flame tilt angle increases with an increase of Ri-1. The temperatures of hot gases in the fire room decrease due to the cooling effect of fresh air induced by stack effect. The mass loss rate of methanol fuel is influenced by fresh air flow sucked into fire room due to stack effect. On the basis of the experimental results, we conclude that the velocity of air flow into fire room is proportional to 1/3 power of the heat release rate in the stairwell.